Geographic information system-based comprehensive oil spill risk assessment in China’s Bohai Sea - Wang, Yebao; Du, Peipei; Liu, Baijing; Wu, Xiaoqing (Frontiers in Marine Science, 2023)
The Chinese Bohai Sea is a semi-enclosed, highly vulnerable continental sea that is exposed to the risk of oil spills due to offshore oil and gas activities. In this study, a geographic information system (GIS)-based “tanks–pipelines–platforms–ships–channels” (TPPSC) comprehensive framework, including a storage tank indicator, a pipeline indicator, a platform indicator, a ship indicator, and a channel indicator, was built to analyze the comprehensive marine oil spill risk in the Bohai Sea and to show the spatial differentiation of risk using GIS and the entropy weight method (EWM). The proposed method will overcome the shortcomings of the traditional statistical and scenario analysis theories. The results show that extremely high-risk areas are mostly located in Liaodong Bay and Bohai Bay; high-risk areas are located in the Bohai Strait and on the north side of the Shandong Peninsula; moderate-risk areas are mainly located on both sides of the Bohai Strait; low-risk areas are located on the south side of Liaodong Bay, in the middle of the Bohai Strait, and in Laizhou Bay; and extremely low-risk areas are located on the west side of Bohai Bay, the south side of Laizhou Bay, and the middle of the Bohai Sea. This framework demonstrated the applicability of the new risk assessment model, and the evaluation tests provided useful information for future research on marine oil spill risk management.